Perancangan Aplikasi Sistem Keamanan Checkout Online Shop - Viencent; Cokorda Pramartha (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2023)
Online shopping has become a preferred choice for many people to meet their consumer needs. However, security issues in online transactions remain a major concern, especially when unauthorized checkouts occur without the account owner’s knowledge. To address this problem, this research aims to design an online shop checkout security application. The application ensures that each checkout is performed by the account owner and not by unauthorized individuals, such as children without their parent’s knowledge. Advanced technology approaches and appropriate security methods will be employed in the design of this application, including the use of two-factor authentication and verification through unique security codes. It is expected that this application will provide additional protection to online shop users in maintaining the security and integrity of their transactions.